"Ethics drills": how to train your ethical muscle for the (un)foreseeable - Clemente, Marco (Organizational corruption, crime and COVID-19, 2025)
Despite the growing research, teaching, and training efforts to improve ethical behaviors in organizations, instances of misconduct and corruption are still daily news. Limitations in the current way we teach and train about ethical situations are known. One of the main challenges is using theoretical or scenario-based training, where people may act differently compared to real-life situations. This becomes even more apparent during crises, such as the Covid-19 pandemic, where emotional and cognitive capabilities are under stress, which can result in a surge of unethical behavior. Building on the analogy of “fire drills,” where participants are asked to make demanding decisions in realistic settings, we propose the idea of “ethics drills” to assess and train the behavior of participants in complex, real-life ethical situations. We argue that ethics drills can be helpful in training anti-corrupt behavior and raising employees’ awareness of ethical issues, especially during crises such as the Covid-19 pandemic. In this chapter, we review the literature on ethics teaching and training to identify current challenges. We then show how the introduction of “ethics drills” can help address such limitations. We conclude by discussing the ethical aspects of running such ethics drills for the company and its participants.